THE ROLE OF TECHNOLOGY IN SELF-STUDY ENGLISH LEARNING OF PHARMACY STUDENTS (Universal International Scientific Journal, 2026)
This article explores an innovative methodology for independent study of Englishfor pharmacy students. This method is aimed at solving the problems of selecting educationalmaterials and consolidating acquired knowledge that pharmacy students face in independent study ofEnglish. This method consists of two stages, which include visual information acquisition viaYouTube and interactive reinforcement using generative artificial intelligence. This not only increasesthe effectiveness of language learning, but also helps the student develop critical thinking andconsolidate his knowledge.
Keywords: pharmacy students; student autonomy; YouTube